Classes de declive e unidades de solo da bacia do rio Capivara - Botucatu (SP) - Araújo Júnior, Armindo Alves de; Campos, Sérgio; Barros, Zacarias Xavier de; Cardoso, Lincoln Gehring (IRRIGA, 2000)
Classes de declive e unidades de solo da bacia do rio Capivara - Botucatu (SP)